Public Opinion in Karanganyar Regency on The Preventive Function of The Public Prosecutor's Office in Efforts to Control and Enforce Criminal Acts - Berliana Kinanthi Mukti; K Kuswardani (Proceeding International Conference Restructuring and Transforming Law, 2024)
This research was prepared with the aim of obtaining information about the opinion of the community, especially the Karanganyar District community, Karanganyar Regency, regarding the application of the function of law enforcement officials in this case the public prosecutor's office, namely the preventive function as an effort to prevent criminal acts in the community. The research uses a sociological approach in the context of empirical law involving empirical data analysis to understand legal phenomena in society. In addition, the statutory approach is used to analyze the relevant legal framework. The data collection techniques used are interview techniques with randomly selected respondents from the Karanganyar District community of Karanganyar Regency and literature study techniques from primary data in the form of laws and regulations and legal events. Unlike the journal of Education and Development Institut Pendidikan Tapanuli Selatan, entitled "Fungsi Preventif Seksi Pengamanan Pembangunan Strategis Pada Kejaksaan Tinggi Nusa Tenggara Barat Dalam Tindak Pidana Korupsi", that this research focuses on the opinion of the people of Karanganyar District, Karanganyar Regency towards the public prosecutor's office in general in the context of preventive efforts and how regulations in positive law in Indonesia regulate the preventive function of the public prosecutor's office. That in this study the policy regarding the preventive function of the public prosecutor's office has been regulated in Article 30 paragraph (3) of the Law of the Republic of Indonesia Number 16 of 2004 concerning the Public Prosecutor's Office of the Republic of Indonesia and also the Regulation of the Attorney General of the Republic of Indonesia Number Per-006/A/JA/07/2017 concerning Organization and Work Procedures of the Public Prosecutor's Office of the Republic of Indonesia. In fact, the public prosecutor's office has not worked optimally in order to improve this function based on several opinions from people who have never received face-to-face information directly in their neighborhood.